Inversion Properties of n-Alkane Phosphonic Acids Stabilized Emulsions: HLB Dependence - Verdinelli, Valeria (2009)
The emulsifier properties of n-alkane phosphonic acids (C10H21PO3H2; C12H25PO3H2 and C13H27PO3H2) and their mono- and di-sodic salts were studied, with emphasis on the morphological and dynamical inversion properties as a function of their neutralization degree. Maximum stabilization properties were appreciated for C10PO3H2 and C12PO3H2 while not for C13PO3H2. Such fact is associated to their odd number of carbon atoms chain, which is the origin of the intrachain constraints on the tail-chain flexibility. © Taylor & Francis Group, LLC.